Bangunan peninggalan produk akulturasi memerlukan tindakan pelestarian - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Pengabdian Kepada Masyarakat UGM, 1998)
ABSTRACT Presently, mixed architecture style between local style and non-local style, called "indiesch architecture", has broadly been discussed. However, the fact is that many buildings with non-local or non-genuine Indonesian architecture style have been destroyed. It is questionable, weather this action is right. What are the strengths of "indiesch architecture"? Studies on the existence of the non-local architecture style, and the comparison between that style and the local style been conducted and developed. Those studies found that the non-local architecture style has influenced the development of the local style. Therefore, concern on the existence of buildings with indiesch architecture style as a heritage culture of Indonesia is needed, and more detailed study on the non-local architecture style is important to be done.